Odpowiedź i szczegółowe wyjaśnienie:
[tex]\sqrt[3]{2000}-\sqrt[3]{250}=\sqrt[3]{1000\cdot2}-\sqrt[3]{125\cdot2}=\sqrt[3]{10^2\cdot2}-\sqrt[3]{5^3\cdot2}=\\\\=10\sqrt[3]2-5\sqrt[3]2=5\sqrt[3]2\\\\\\\sqrt[3]{3000}+\sqrt[3]{24}-\sqrt[3]{81}=\sqrt[3]{1000\cdot3}+\sqrt[3]{8\cdot3}-\sqrt[3]{27\cdot3}=\\\\=\sqrt[3]{10^3\cdot3}+\sqrt[3]{2^3\cdot3}-\sqrt[3]{3^3\cdot3}=10\sqrt[3]3+2\sqrt[3]3-3\sqrt[3]3=9\sqrt[3]3\\\\\\\sqrt[3]{7000}-\sqrt[3]7=\sqrt[3]{1000\cdot7}-\sqrt[3]7=\sqrt[3]{10^3\cdot7}-\sqrt[3]{7}=10\sqrt[3]7-\sqrt[3]7=9\sqrt[3]7[/tex]